Anticipation and situation-assessment skills in soccer under varying degrees of informational constraint - Basevitch, I.; Tenenbaum, G.; Filho, E.; Razon, S.; Boiangin, N.; Ward, P. (Journal of Sport & Exercise Psychology, 2020)
The authors tested the notion that expertise effects would be more noticeable when access to situational information was reduced by occluding (i.e., noncued) or freezing (i.e., cued) the environment under temporal constraints. Using an adaptation of tasks developed by Ward, Ericsson, and Williams, the participants viewed video clips of attacking soccer plays frozen or occluded at 3 temporal points and then generated and prioritized situational options and anticipated the outcome. The high-skill players anticipated the outcomes more accurately, generated fewer task-irrelevant options, and were better at prioritizing task-relevant options than their low-skill counterparts. The anticipation scores were significantly and positively correlated with the option prioritization and task-relevant options generated but not with the total options generated. Counter to the authors` prediction, larger skill-based option-prioritization differences were observed when the play was frozen than when it was occluded. These results indicate that processing environmental information depends on temporal and contextual conditions.